Enhancing pronunciation skills in ESL learners through chatgpt: The efficacy of an ai-driven learning tool - Priscilla Shak; Chang, Siew Lee; Daron Benjamin Loo (Universiti Sains Malaysia, 2025)
Pronunciation is often taken as a gauge of language proficiency and to judge overall English ability—sometimes inaccurately. As ESL learners reach tertiary-level education, pronunciation training often diminishes in priority, as they are assumed to have mastered basic pronunciation skills. Unfortunately, this may not be the case, and many pronunciation errors persist into adulthood. If this remains unaddressed, they can become fossilised, making them more challenging to correct later. In higher education settings, English language courses rarely focus on pronunciation training, particularly in the context of correcting erroneous pronunciation. This neglect can lead to communication issues and negatively impact individuals' growth and others’ perception of them in professional environments. Despite the potential of AI technology to transform language learning, there is a notable gap in the literature regarding the application of AI tools for pronunciation enhancement. This study aims to bridge this gap by investigating the use of ChatGPT for individualised pronunciation learning. It positions the study as a critical step toward enabling ESL learners to leverage the use of AI-driven approaches as potential solutions for pronunciation enhancement. Conducted among undergraduates taking English courses in a public university in Malaysia, this study adopts a quasi-experimental mixed-method design involving pre-test, post-test, and vocabulary identification. Findings indicated that ChatGPT has great potential for applications in pronunciation learning and can offer individualised self-accessed support for ESL students to improve their pronunciation.